«Заборонений»: Стус кінематографічний - Пуніна, О. (Слово і Час, 2022)
Проаналізовано образ Василя Стуса в художньому фільмі Романа Бровка
«Заборонений» (2019). З’ясовано, якими засобами режисер утілює психологічну структуру індивідуальності у стрічці для широкої глядацької аудиторії. Психологічний чинник кінематографічного образу ґрунтується на
рисах характеру, поведінці, притаманній Стусові-людині: він схильний
до експансивної реакції, непристосований до компромісів, самодостатній,
сильної волі. Режисер працює як у формальній площині (принцип градації,
протиставлення, кінематографічний засіб образу-переживання, загальний план), так і в змістовій (домислені епізоди й персонажі, закадрові читання віршів, сконденсований зміст мотто, уведення авторського тексту в новий контекст тощо). The paper reviews the image of Vasyl Stus in Roman Brovko’s feature film “The Proscribed”
(“Zaboronenyi”, 2019). The researcher aims to find out how the director embodies the psychological
structure of the writer’s personality in the film for a wide audience. To do this, the
author of the paper uses interviews with the director, the leading actor, and contemporaries
of Vasyl Stus, analyzing the feature film from the perspective of its form, content, and meaning.
The members of the production team emphasized the reactions of the creative person to
untruth and injustice; they focused on such traits of Stus’s character as being extremely honest,
caring, and emotionally explosive. Stus’s contemporaries, watching the film first, noted
the emotional side as successfully embodied on the screen.
The psychological component of Vasyl Stus’s cinematographic personality is based on the
character traits, reactions, and behavior inherent to real Stus: the protagonist is prone to
impetuous reactions, not suited to compromises, self-sufficient, and strong-willed. To create
such a psychological structure of Vasyl Stus’s character in “The Proscribed”, the director
works both with the form (he uses the principles of gradation and opposition, the means of
image-experience, and a wide shot) and content (imaginary episodes, reading poetry behind
the scenes, condensed meaning of the epigraph, some fictional characters, the author’s text
in a new context, etc.). These efforts give the opportunity to see the movie character of Vasyl
Stus with his inherent emotional reactions (impetuous) and feelings (protest, anger, justice),
moral and ethical guidelines (to give much, to be humane and do good), and the high level
of self-awareness.